2019
DOI: 10.1242/jcs.222802
|View full text |Cite
|
Sign up to set email alerts
|

Ankyrin-G induces nucleoporin Nup358 to associate with the axon initial segment of neurons

Abstract: Nup358 (also known as RanBP2) is a member of the large nucleoporin family that constitutes the nuclear pore complex. Depending on the cell type and the physiological state, Nup358 interacts with specific partner proteins and influences distinct mechanisms independent of its role in nucleocytoplasmic transport. Here, we provide evidence that Nup358 associates selectively with the axon initial segment (AIS) of mature neurons, mediated by the AIS scaffold protein ankyrin-G (AnkG, also known as Ank3). The N-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 90 publications
(122 reference statements)
2
11
1
Order By: Relevance
“…We immunostained cultured hippocampal neurons at 10 days in vitro (DIV). Consistent with previous reports (Hamdan et al, 2020;Khalaf et al, 2019), the anti-Ranbp2 antibody (A301-796A) labeled nuclei, but also colocalized with AnkG at the AIS (Fig. 1A).…”
Section: The Anti-ranbp2 Antibody (A301-796a) Detects Ranbp2 and Neurofascinsupporting
confidence: 92%
See 4 more Smart Citations
“…We immunostained cultured hippocampal neurons at 10 days in vitro (DIV). Consistent with previous reports (Hamdan et al, 2020;Khalaf et al, 2019), the anti-Ranbp2 antibody (A301-796A) labeled nuclei, but also colocalized with AnkG at the AIS (Fig. 1A).…”
Section: The Anti-ranbp2 Antibody (A301-796a) Detects Ranbp2 and Neurofascinsupporting
confidence: 92%
“…Given the potential link of Ranbp2 to the microtubule-based cytoskeleton, and the number of microtubule-associated proteins that regulate AIS function (Leterrier, 2018), we sought to determine the function of Ranbp2 at the AIS. However, we found that the anti-Ranbp2 antibody used in both previous studies, and that labels AIS (Hamdan et al, 2020;Khalaf et al, 2019), is not specific to Ranbp2. Instead, it cross-reacts with neurofascin (Nfasc).…”
Section: Introductioncontrasting
confidence: 56%
See 3 more Smart Citations